Isolation and Characterisation of a Sesquiterpene from Lactuca indica - Song Fan, Ming; Ye, Guan; Gang Huang, Cheng (Asian Journal of Chemistry, 2010)
A new sesquiterpene lactone glycoside, named Lactuside D, was isolated from Lactuca indica. Spectral analysis studies suggested the compound as 3(4),11(13)-dien-eudesma-5α,6β,7αH-12,6-olide-15-O-β-D-glucopyranoside-1-β-p-hydroxy-phenyl-acetate.